Investigation of FexCo1-xSb3 thin films as a Skutterudite and determination their specific resistance - دلا ايهم (Latakia University Journal -Basic Sciences Series, 2023)
In this paper the thin films FexCo1-xSb3 are investigated as a skutterudite and showed some of its properties and applications: Seebeck effect, Peltier effect and the specific resistance. The aim of this paper is determination the specific resistance of FexCo1-xSb3 thin films using the four probe method. This method was employed by using two devices in two different countries and the results was compared.